Motions: Exploring Human-Information Interactions Beyond Clicks - Kohler-Casasempere, J; Gonzalez-Ibanez, R (IEEE Computer Society, 2020)
During the last decades, the way people interact with information has drastically changed as a result of the rapid proliferation of new technologies and the arrival of the World Wide Web. This technological evolution has propitiated a transition from physical information objects such as books to their digital and ethereal versions as a result, an interaction gap between individuals and information objects has emerged as new technologies appear, alternative possibilities to interact with information can be envisioned, however, little is known about the benefits and costs of such interaction forms (e. g. body-based, virtual and augmented reality, among others). Furthermore, the complexity and cost of conducting studies with technologies such as the above mentioned can be particularly high. To address these problems, we introduce MOTIONS (huMan-infOrmation inTeractION System), a system to conduct evaluations and experiments on human-information interactions with multiple types of interfaces additionally, we present a synthesis of case studies conducted using MOTIONS with the aim to compare different types of interactions with digital information objects. On the one hand, these studies demonstrate MOTIONS utility as a research tool. On the other hand, results suggest that state-of-The-Art interaction technology, while appealing, may not be necessarily cost-effective in terms of performance and user experience these results shed light not only about potential uses of MOTIONS, but also about design decisions when developing new interfaces to interact with information objects in the digital realm. © 2020 IEEE.